Factors promoting the education of pregnant high school students and adolescent mothers: A qualitative comparative study in Argentina and South Africa - Alvarez, Almada Adriana (Department of Social Development, 2025)
Adolescent pregnancy represents a significant challenge in Latin America, and sub-Saharan Africa, often leading to girls dropping out of school, limiting their future opportunities. This study explored positive factors on the school retention of high school pregnant learners and adolescent mothers in Argentina and South Africa, focusing on school and NGO strategies relevant to development contexts. This study used a qualitative research approach with an exploratory design and employed purposive sampling techniques. Five NGO staff in Argentina and four in South Africa, as well as four school staff in Argentina and four in South Africa, participated in semi-structured interviews. Data analysis followed Tesch's steps for organising unstructured qualitative data, where transcripts were reviewed to identify and categorise themes by frequency, relevance, and connections, and then compared across both countries. The research findings revealed that structural issues, such as poverty and lack of access to social services, increase dropout risks for adolescent mothers, along with inadequate support from school and their broader environments. Prevention strategies in both countries include sexual reproductive education, raising awareness, and support networks. In South Africa, additional efforts emphasise providing information and parenting skills, while in Argentina, the focus is on early identification of learners' needs and the school provision of accommodations. Finally, the study found that positive experiences were determined by a support network, and customised and comprehensive support. In South Africa, fostering a sense of purpose emerged as a significant factor, and in Argentina, the flexibility in re-entry policies results in educational engagement. Recommendations provided were for schools, NGOs, and policymakers to create strong support networks, and adapt schools'systems to accommodate the diverse needs of learners. Future research should focus on the needs of adolescent fathers, flexible approaches in schools, and strategies for academic success of pregnant learners and adolescent mothers. In summary, this research study has provided insight into the determinants that facilitate the schooling of pregnant learners and adolescent mothers.